Decreased COPD prevalence in Sweden after decades of decrease in smoking. - Backman, Helena; Vanfleteren, Lowie; Lindberg, Anne; Ekerljung, Linda; Stridsman, Caroline; Axelsson, Malin; Nilsson, Ulf; Nwaru, Bright I; Sawalha, Sami; Eriksson, Berne; Hedman, Linnea; Rådinger, Madeleine; et al. (Respiratory Research, 2020)
BACKGROUND: COPD has increased in prevalence worldwide over several decades until the first decade after the millennium shift. Evidence from a few recent population studies indicate that the prevalence may be levelling or even decreasing in some areas in Europe. Since the 1970s, a substantial and ongoing decrease in smoking prevalence has been observed in several European countries including Sweden. The aim of the current study was to estimate the prevalence, characteristics and risk factors for COPD in the Swedish general population. A further aim was to estimate the prevalence trend of COPD in Northern Sweden from 1994 to 2009. METHODS: /FVC < lower limit of normal (LLN) criterion. RESULTS: Based on the fixed ratio definition, the prevalence of COPD was 7.0% (men 8.3%; women 5.8%) in 2009-2012. The prevalence of moderate to severe (GOLD ≥ 2) COPD was 3.5%. The LLN based results were about 30% lower. Smoking, occupational exposures, and older age were risk factors for COPD, whereof smoking was the most dominating risk factor. In northern Sweden the prevalence of COPD, particularly moderate to severe COPD, decreased significantly from 1994 to 2009, and the decrease followed a decrease in smoking. CONCLUSIONS: The prevalence of COPD has decreased in Sweden, and the prevalence of moderate to severe COPD was particularly low. The decrease follows a major decrease in smoking prevalence over several decades, but smoking remained the dominating risk factor for COPD.